2007
DOI: 10.1186/1471-2458-7-260
|View full text |Cite
|
Sign up to set email alerts
|

Erosive Arthropathy in systemic sclerosis

Abstract: Background: To determine radiological features of arthropathy in systemic sclerosis patients with polyarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 15 publications
5
17
1
1
Order By: Relevance
“…Meanwhile, Allali et al found radiographic changes in 80% of 46 patients with SSc who had arthritis, including joint space narrowing in 37% and erosions in 43% of these patients. 9 The same researcher found that the most common sites of occurrence of erosions were the proximal interphalangeal and radiocarpal joints. 9 In a cohort of 58 patients with SSc, Schmeiser et al found signs of arthritis in 31% of patients, with 19% being clinical and 26% radiological.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Meanwhile, Allali et al found radiographic changes in 80% of 46 patients with SSc who had arthritis, including joint space narrowing in 37% and erosions in 43% of these patients. 9 The same researcher found that the most common sites of occurrence of erosions were the proximal interphalangeal and radiocarpal joints. 9 In a cohort of 58 patients with SSc, Schmeiser et al found signs of arthritis in 31% of patients, with 19% being clinical and 26% radiological.…”
Section: Discussionmentioning
confidence: 96%
“…9 The same researcher found that the most common sites of occurrence of erosions were the proximal interphalangeal and radiocarpal joints. 9 In a cohort of 58 patients with SSc, Schmeiser et al found signs of arthritis in 31% of patients, with 19% being clinical and 26% radiological. In a meta-analysis of seven studies, we found a prevalence of 26% of radiologically detectable arthritis in patients with SSc.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…While erosive arthritis can occur rarely in SSc [6], our patient had only Raynaud phenomenon and displayed no other features of SSc. He does fulfill 5 of the 7 ACR criteria for rheumatoid arthritis (RA).…”
Section: Discussionmentioning
confidence: 93%